Milton and the Zohar - Melnick, Alan (Department of English Language and Literature, 2016)
This research is a comparative investigation of Milton and the Zohar divided into six Chapters. The similarities in ideas are discussed and possible indebtedness to the Kabbalah is duly noted where appropriate. In Chapter One the central symbolical code of the 'tree of life' is related to the philosophical structure of Paradise Lost and Camus, divided into the ensuing sections: intellect and passion; beauty; justice and mercy; intellect and intuition; the crown; the evolution of man and the journey from sephirot to sephirot; the four worlds in the universe and the three aspects of the soul. Chapter Two is concerned with the creation of the universe and due attention is given to the following: the revelation of the future to Adam; the emanation of matter from God; the process of creation from darkness; the transcendence of God; the existence of sin or the need to justify creation; the creation of Adam; the implied creation of Adam as an androgynous being; the sexuality of the stars and other planets; creation based on duality; creation as an emanation from thought; the loss of direct communication with God. In Chapter Three the fall from a paradisal innocence and the position on marital affairs. in Milton's works and the Zahar is investigated including: the victory of carnal appetite over the higher mind; seduction in Samson Agonistes; the transformation of Adam's and Eve's ethereal bodies after the fall; 'appetite' while in the Garden; attitudes towards divorce; soul mates; procreation. In Chapter Four the discussion includes reference to Satan or Samael in the Zahar and the ensuing sections: a comparison between Sin and Lilith; the fallen angel Azazel; the goat as an evil animal; the 'evil eye'; Adramelec and Balaam; the sorcery of Balak (the demonic bird). Chapter Five continues with an investigation of the left-hand path or sitra-ahra focusing on: hell as a locality; hell as a psychological reality within the individual; hell as the 'shadow' within the subconscious; the left-hand path and judgement; Satan, Samael and Hitler; the chariot of paternal deity. In the final Chapter various aspects of the Messianic kingdom are considered: the apocalypse and the millenium; the arbor vitae of Eden and the second paradise; the promise of a future redeemer foretold by Michael or Raziel; the removal of evil from earth; the coming of the Messiah as a cosmic cycle or shemittah; the rainbow as a herald of peace.